Purification of Biodiesel from Waste Cooking Oil Using Bentonite as Dry Washing Agent - Suriaini, Nanda; Febriana, Tika Thalia; Yulanda, Andesta; Adisalamun, Adisalamun; Syamsuddin, Yanna; Supardan, Muhammad Dani (Jurnal Rekayasa Kimia & Lingkungan, 2019)
The process of biodiesel purification is an important step in getting biodiesel products that meet specifications as a substitute for fossil-based fuels. Dry washing method has been developed to achieve an effective purication strategy in order to produce high-quality biodiesel. Bentonite can be used as dry washing agent because it has a good adsorbing properties as well as a large pore and surface area therefore can attract polar substances such as glycerol and methanol. The purpose of this research is to know the capability of activated bentonite as dry washing agent for purification of biodiesel produced from waste cooking oil. The activation process of bentonite was carried out using sulfuric acid with concentration 1.5 M. Characterization of the bentonite was conducted using X-Ray Diffraction (XRD) for minerals content and BrunauerEmmettTeller (BET) method for surface area. Bentonite was used as dry washing agent for biodiesel purification by varying washing time (10, 20, 30, 40 and 50 minutes) and adsorbent amount (1, 2, 3, 4 and 5%). The experimental results showed that purification of biodiesel by dry washing using activated bentonite resulted in a better yield and quality than wet washing and dry washing using non-activated bentonite, except the acid number. The best operation condition resulted from this research is at 10 minutes washing time and 1% adsorbent with yield of 94.1%; acid number of 0.4208 mg KOH/gram; density of 0.8838 gram/cm3, viscosity of 3.0617 mm2/s and water content of 1.17%.